Development of a Lepto-IgM EIACR test to diagnose leptospirosis disease in Costa Rican patient samples. - Valverde J, María de los A; León, Bernal; Taylor, Lizeth; Visona, Kirsten (Investigación Clínica, 2009)
Leptospirosis is an endemic disease throughout Costa Rica, which could be misdiagnosed because manifestations of this febrile disease may vary from mild flu-like symptoms to severe illness involving vital organs such as liver and lungs. Therefore an early specific diagnosis is important to ensure a favorable clinical outcome. The purpose of this study was to develop a Leptospira sp. anti-IgM EIA (Lepto-IgM EIACR) test and to compare it using Lepto-Dipstick IgM (Lepto-DS IgM) and PanBio-EIA IgM with the Microscopy Agglutination test (MAT) as a reference assay. Sera from 736 healthy blood donors were used as negative controls to calculate specificity (97.1%), Confidence Interval 95 (CI (96-98). Cross reactivity was evaluated in 268 patient samples with 6 different diseases. Dengue and measles had the highest cross reactivity (16%) while rubella showed the lowest (3%). To determine the sensitivity of the Lepto- IgM EIACR, 33 samples positive by MAT of 96 paired samples from patients with symptoms related to leptospirosis infection were tested. Lepto-IgM EIACR reached a sensitivity of 90.9% (CI 81-100), while Lepto-DS IgM was 48.5% (CI (31-66). The most frequent serovars detected by MAT in these paired samples were Hebdomadis 14.7%, Hardjo 11.8%, Pomona 8.8% and Icterohaemorrhagiae 5.9%. Furthermore 59 febrile patient samples were tested initially with PanBio-EIA IgM, 21 samples (35%) were positive. When these samples were re-tested by Lepto-IgM EIACR and Lepto-DS IgM, 80.9% and 33% were positive, respectively. The results of the evaluation indicate that Lepto-IgM EIACR test could be a good alternative to detect acute leptospirosis in Costa Rica.